Social Economic Analysis Of Women's Role In Informal Sector House: Case Study: Ibu Nyai , Babakan Lebak Village, Dramaga, West Java - Sadiqin, Amin (CV ODIS, 2021)
Differences in the division of labor within the household are often one of the issues discussed. Women are considered to do more double work roles than men. This can be seen from the many activities carried out by women ranging from cooking, washing, caring for children, to working. In this study, the authors intend to find out how the pattern of division of labor, access, and control of resources, as well as daily activities of a woman and a man from a family. The focus of this research is on household assistants who work in the informal sector and double work in the Babakan Lebak Village area, Dramaga, Bogor. In addition, the factors that influence these things also want to be known by the author. The method used in this research is the qualitative method. Case studies, observations, and in-depth interviews were conducted in this study which was then analyzed using Harvard's gender approach. The results of this study indicate that women hold more multiple roles than men. The role of access has the same access between men and women. The supporting factors are economic, socio-cultural, religious, and environmental patterns.